Photo-thermal dual-curing polymer concrete material as well as preparation method and application thereof

Through light-heat dual-curing polymer concrete materials, the synergistic effect of ultraviolet light and thermal initiators is used to solve the problem of reaction termination of traditional building materials in extreme environments, enabling 3D printing of complex unsupported structures with high strength mechanical properties.

CN119330634APending Publication Date: 2025-01-21SOUTHEAST UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411457804.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Traditional building materials have termination of reactions and performance failures in extreme environments such as high vacuum and large temperature difference, and it is difficult to achieve unsupported 3D printing of complex structures.

Method used

The light-heat dual-curing polymer concrete material is used, and through the synergistic effect of ultraviolet photoinitiator and thermal initiator, rapid light curing and subsequent thermal curing of the material are achieved, the viscosity is reduced and the amount of inorganic filler is increased.

Benefits of technology

It achieves stable solidification of materials in extreme environments, can print complex unsupported structural parts, has high compressive and flexural strength, and is suitable for harsh environments such as the moon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090976130000061
    Figure BDA0005090976130000061
  • Figure BDA0005090976130000071
    Figure BDA0005090976130000071
  • Figure HDA0005090976140000011
    Figure HDA0005090976140000011
Patent Text Reader

Abstract

The invention provides a light-heat dual-curing polymer concrete material as well as a preparation method and application thereof. The material is prepared from the following components in parts by mass: 65 to 75 parts of fine aggregate, 25 to 35 parts of polymer monomer, 0.75 to 2.8 parts of photoinitiator and 0.85 to 2.8 parts of thermal initiator. Wherein the polymer monomer contains an epoxy functional group and an unsaturated double-bond functional group, not only can be subjected to cross-linking polymerization with the photoinitiator, but also can be subjected to ring-opening polymerization with the thermal initiator. The material is low in viscosity, and the normal-temperature viscosity is only 1 Pa.s, so that the content of bonded aggregate can be increased. The surface of the printing strip is rapidly cured to form a hard shell structure in combination with an ultraviolet light-assisted 3D printing technology, the slurry in the printing strip is heated and cured to achieve complete hardening, finally, the unsupported structural part which is excellent in mechanical property and complex in shape is obtained, and the unsupported structural part is suitable for being applied to severe environments such as the moon with the low vacuum degree, the large temperature difference and even the low-gravity condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a light-heat dual-curing polymer concrete material and a preparation method and application thereof, belonging to the technical field of building materials. Background Art

[0002] In recent years, a number of extraterrestrial exploration programs, such as the United States' "Artemis Project", China's "Chang'e Project" and Russia's "Moon Project", have been proposed one after another, aiming to establish research stations in extraterrestrial space by around 2030. Among them, the moon and Mars have become the main targets of attention, especially the moon, which is often regarded as the preferred location for establishing an outpost. However, extreme conditions such as high vacuum and large temperature difference in the lunar environment pose great challenges to building materials and construction technology. Considering these needs and limitations, unmanned 3D printing technology is considered to be an important means to achieve extraterrestrial construction because of its advantages such as no need for templates, fast construction, cost and time savings, and the ability to print complex structures. Traditional building materials such as cement and concrete are widely used in the field of 3D printing because of their cheap availability and mature research. However, these materials harden through the slow hydration of cement, and require water as a transmission, dispersion and reaction medium. The setting speed is slow, and the slurry has almost no strength before hardening. Under high vacuum and high temperature environments, water is very easy to volatilize, resulting in the termination of the reaction of traditional building materials and the failure of performance. Therefore, it is urgent to find materials that can adapt to extreme environments, can use 3D printing construction processes and have excellent strength.

[0003] Polymer binders have flexible design and excellent mechanical properties. Rapid curing and molding can effectively solve the problem of adhesive volatilization in vacuum and large temperature difference environments. Using its excellent bonding properties to bond in-situ aggregates can be a powerful choice for construction in extreme environments. Among them, photosensitive resins will produce active groups under the action of ultraviolet light, triggering the rapid polymerization of prepolymers or monomers. The reaction speed is extremely fast and can be completed instantly. Photosensitive resins usually contain ultraviolet-active prepolymers or monomers and photoinitiators. However, when used as building materials, a large volume of fillers needs to be added, resulting in opacity of the slurry, insufficient internal light, and inability to polymerize the internal materials. Only the curing of the surface area can be achieved to inhibit the volatilization of the internal materials and maintain the stability of the materials in extreme environments. For the internal areas that have not been exposed to light, additional curing mechanisms are required to achieve the curing of the internal materials to further improve their mechanical properties and achieve a balance between rapid prototyping and mechanical properties. In view of the temperature range of extreme environments such as the moon, the rational use of high temperature environments to achieve internal curing through thermal curing can effectively reduce energy consumption.

[0004] At present, the method of applying polymer concrete to extreme environment construction is still in the exploratory stage. CN118290662A discloses a photothermal dual-curing 3D printing resin composite material and its application, and CN118192169A discloses a photothermal curing 3D printing photosensitive resin composition and its printing method at 405nm. Both are photothermal dual-curing 3D printing resin composite materials composed of base resin, photoinitiator, thermal initiator and curing aid. These materials have only been printed on some pure polymer systems, and have failed to solve the 3D printing problem of opaque slurry under large volume filler dosage; CN114350158A discloses a photothermal dual-curing composite direct writing 3D printing medium, preparation method and application, but its viscosity is as high as 200-1000Pas, and the amount of inorganic filler cannot be increased, making it difficult to use for construction purposes. In addition, these materials only achieve the demonstration of simple structures and cannot meet the needs of unmanned construction of complex structures. Therefore, there is an urgent need to develop a polymer concrete system with low viscosity, efficient photocuring, high mechanical strength of thermal curing, and high compatibility with 3D printing, so as to provide new material solutions and technical means to meet the construction challenges in extreme environments. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a light-heat dual-curing polymer concrete material, the second purpose of the present invention is to provide a method for preparing the light-heat dual-curing polymer concrete material, and the third purpose of the present invention is to provide an application of the light-heat dual-curing polymer concrete material in unsupported 3D printed buildings.

[0006] Technical solution: The light-heat dual-curing polymer concrete material described in the present invention includes the following components in a mass fraction ratio: fine aggregate: polymer monomer: photoinitiator: thermal initiator is 65-75: 25-35: 0.75-2.8: 0.85-2.8.

[0007] Furthermore, the light-heat dual-curing polymer concrete material comprises the following components in a mass fraction ratio: fine aggregate: polymer monomer: photoinitiator: thermal initiator is 70:27.4:1.6:1.

[0008] Furthermore, the polymer monomer is an alicyclic epoxy resin.

[0009] Furthermore, the polymer monomer is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate.

[0010] Furthermore, the photoinitiator is at least one selected from onium salt cationic photoinitiators.

[0011] Furthermore, the onium salt cationic photoinitiator is at least one selected from triphenyl hexafluoroantimonate sulfonium salt, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, p-toluenesulfonium salt, phenyldimethyl iodonium salt, phenethyl iodonium salt or p-toluene iodonium salt. Triphenyl hexafluoroantimonate sulfonium salt is preferred.

[0012] Furthermore, the thermal initiator is at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or boron trifluoride-monoethylamine complex, preferably boron trifluoride-monoethylamine complex.

[0013] Furthermore, the fine aggregate is one or a mixture of basalt powder, cement, mineral powder, fly ash or ceramic powder, preferably basalt powder or ceramic powder.

[0014] The preparation method of the light-heat dual-curing polymer concrete material of the present invention comprises the following steps: mixing polymer monomers, photoinitiators and thermal initiators to obtain a mixed liquid, adding fine aggregate to the mixed liquid, and continuing to stir until the slurry is evenly mixed.

[0015] Furthermore, during the preparation, the preparation environment temperature is 15-25° C., and the stirring speed is 400-500 rpm.

[0016] Application of the light-heat dual-curing polymer concrete material of the present invention in 3D printing.

[0017] The present invention also includes a method for 3D printing using the light-heat dual-curing polymer concrete material of the present invention, comprising the following steps:

[0018] (1) The 3D printer extrusion nozzle is equipped with a UV light source;

[0019] (2) When the light-heat dual-curing polymer concrete material of the present invention is immediately exposed to ultraviolet radiation after being extruded from the nozzle of the 3D printer, the area on the surface exposed to ultraviolet radiation immediately starts a photocuring reaction to obtain a photocured molded specimen;

[0020] (3) The photocurable molded specimen obtained in step (2) is heated for post-thermal curing treatment to ensure that the areas inside the printed specimen that are not exposed to ultraviolet light are completely cured.

[0021] Furthermore, in step (1), the wavelength of the ultraviolet light source is 300-400 nm, preferably 365 nm.

[0022] Furthermore, in step (2), when the ultraviolet radiation distance is 2 cm, the light intensity of the ultraviolet radiation is 5000 W / cm 2 , the ultraviolet radiation time is within 13s.

[0023] Furthermore, in step (3), the temperature of the thermal curing post-treatment is 80 to 120° C., and the time of the thermal curing post-treatment is within 35 minutes.

[0024] The polymer monomer used in the present invention contains epoxy functional groups and unsaturated double bond functional groups, which can undergo cross-linking polymerization with photoinitiators and ring-opening polymerization with thermal initiators. The designed light-heat dual-curing polymer cement-based material has low viscosity, with a room temperature viscosity of only 1Pa·s, which is beneficial to increasing the content of bonding fine aggregate. The present invention combines ultraviolet-assisted 3D printing technology, and utilizes a photocuring mechanism to induce the surface of the print bar to rapidly cure to form a hard shell structure, thereby providing early support strength and maintaining a stable print bar shape. The slurry inside the print bar that is not exposed to ultraviolet light is completely hardened under the heated post-curing mechanism, and finally a support-free structural part with excellent matrix mechanical properties and complex shape is obtained, which is suitable for use in harsh environments such as the moon with low vacuum, large temperature differences, and even low gravity conditions.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0026] (1) Strong environmental adaptability: The present invention introduces a light-heat synergistic curing mechanism. In the initial stage, a hard shell structure can be quickly formed on the surface within only 13 seconds through the light curing reaction mechanism, maintaining the shape of the printed strip structure and protecting the stability of the internal material. Compared with traditional cement-based 3D printing materials, it is more suitable for application in harsh environments such as high vacuum and large temperature difference.

[0027] (2) Printing of unsupported structures can be achieved: The present invention relies on the rapid characteristics of early photocuring and can prepare complex unsupported structures such as cantilever beams and springs, greatly extending the scope of practical application.

[0028] (3) Thermal curing efficiency and curing temperature range are controllable and adjustable: The curing temperature of the present invention can be controlled within a wide range of 95-135°C. The curing efficiency is related to the temperature, and the fastest curing time is less than 5 minutes.

[0029] (4) The direct extrusion printing of polymers with high inorganic filler content in the present invention greatly reduces the polymer content and improves the utilization rate of in-situ materials in extreme environments.

[0030] (5) Excellent mechanical properties of printed structural parts: The 3D printed light-heat dual-curing polymer concrete provided by the present invention has a compressive strength greater than 120 MPa and a flexural strength greater than 48 MPa after complete curing. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a photo of the UV light source assisted 3D printer in Example 6;

[0032] Figure 2This is a diagram of the printing result of the unsupported cantilever beam in Example 6;

[0033] Among them, the print bar widths corresponding to 2.5mm, 5mm and 8mm print heads are 2mm, 4mm and 6mm respectively;

[0034] Figure 3 Printing result diagram of the unsupported spiral sphere in Example 6. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0036] Example 1

[0037] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of triphenylsulfonium hexafluoroantimonate (triphenylsulfonium hexafluoroantimonate, CAS No.: 57840-38-7), 1.5g of boron trifluoride-monoethylamine complex (boron trifluoride ethylamine complex, CAS No.: 75-23-0) as a latent thermal initiator, 128g of basalt powder (particle size distribution 1-300um, median particle size 70um), first stir the other components except the basalt powder at a speed of 400-500rpm for 2min at 15-25℃ until they are uniformly stirred to obtain a mixed solution, then add the basalt powder to the above mixed solution, and continue to stir at a speed of 400-500rpm for 3min until the slurry is uniformly mixed to obtain a light-heat dual-curing polymer concrete slurry.

[0038] Example 2

[0039] The experimental process is the same as in Example 1, except that the cationic photoinitiator is changed to diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, as follows:

[0040] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of cationic photoinitiator diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (CAS No.: 68156-13-8), 1.5g of latent thermal initiator boron trifluoride-monoethylamine complex, 128g of basalt powder, at 15-25°C, stir the other components except basalt powder at a speed of 400-500rpm for 2min until they are uniformly stirred to obtain a mixed solution, then add the basalt powder to the above mixed solution, and continue to stir at a speed of 400-500rpm for 3min until the slurry is uniformly mixed to obtain a light-heat dual-curing polymer concrete slurry.

[0041] Example 3

[0042] The experimental process is the same as in Example 1, except that the latent thermal initiator is changed to methyltetrahydrophthalic anhydride, as follows:

[0043] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of cationic photoinitiator triphenyl hexafluoroantimonate sulfonium salt, 1.5g of methyltetrahydrophthalic anhydride (CAS No.: 5333-84-6) as latent thermal initiator, 128g of basalt powder, and at 15-25°C, stir the other components except the basalt powder at a speed of 400-500rpm for 2min until stirring to obtain a mixed solution, then add the basalt powder to the above mixed solution, and continue stirring at a speed of 400-500rpm for 3min until the slurry is evenly mixed to obtain a light-heat dual-curing polymer concrete slurry.

[0044] Example 4

[0045] The experimental process is the same as in Example 1, except that the fine aggregate is replaced with cement powder, as follows:

[0046] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of triphenyl hexafluoroantimonate sulfonium salt as a cationic photoinitiator, 1.5g of boron trifluoride-monoethylamine complex as a latent thermal initiator, 128g of cement powder (size distribution 1-100um, median particle size 38um), stir the other components except the cement powder at a speed of 400-500rpm for 2min at 15-25℃ until they are evenly stirred to obtain a mixed solution, then add the cement powder to the above mixed solution, and continue stirring at a speed of 400-500rpm for 3min until the slurry is evenly mixed to obtain a light-heat dual-curing polymer concrete slurry.

[0047] Example 5

[0048] The experimental process is the same as in Example 1, except that the latent thermal initiator is a boron trifluoride-monoethylamine complex and the amount is changed to 10 g, as follows:

[0049] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of triphenyl hexafluoroantimonate sulfonium salt as a cationic photoinitiator, 10g of boron trifluoride-monoethylamine complex as a latent thermal initiator, 128g of cement powder (size distribution 1-100um, median particle size 38um), stir the other components except the cement powder at a speed of 400-500rpm for 2min at 15-25°C until stirring to obtain a mixed solution, then add the cement powder to the above mixed solution, and continue stirring at a speed of 400-500rpm for 3min until the slurry is evenly mixed to obtain a light-heat dual-curing polymer concrete slurry.

[0050] Comparative Example 1

[0051] The experimental process is the same as in Example 1, except that no cationic photoinitiator is used, as follows:

[0052] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 1.5g of boron trifluoride-monoethylamine complex as latent thermal initiator, 128g of basalt powder, first stir the other components except basalt powder at a speed of 400-500rpm for 2min at 15-25℃ to obtain a mixed solution, then add the basalt powder to the above mixed solution, and continue stirring at a speed of 400-500rpm for 3min, until the slurry is mixed evenly to obtain a polymer concrete slurry.

[0053] Comparative Example 2

[0054] The experimental process is the same as in Example 1, except that no latent thermal initiator is used, as follows:

[0055] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of cationic photoinitiator triphenylsulfonium hexafluoroantimonate, and 128g of basalt powder. At 15-25°C, stir the other components except the basalt powder at a speed of 400-500rpm for 2 minutes to obtain a mixed solution. Add the basalt powder to the mixed solution and continue stirring at a speed of 400-500rpm for 3 minutes until the slurry is evenly mixed to obtain a polymer concrete slurry.

[0056] Comparative Example 3

[0057] The experimental process is the same as in Example 1, except that the latent thermal initiator is changed to diethyltetramethylimidazole, as follows:

[0058] 50g of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3g of triphenyl hexafluoroantimonate sulfonium salt as a cationic photoinitiator, 3g of diethyltetramethylimidazole thermal initiator, 128g of basalt powder, at 15-25°C, stir the other components except the basalt powder at a speed of 400-500rpm for 2min to obtain a mixed liquid, then add the cement powder to the above mixed liquid, continue to stir at a speed of 400-500rpm for 3min to obtain a mixed liquid, then add the basalt powder to the above mixed liquid, continue to stir at a speed of 400-500rpm for 3min, until the slurry is evenly mixed to obtain a polymer concrete slurry.

[0059] Example 6

[0060] 1. Test of light curing time of polymer concrete paste

[0061] The polymer concrete paste obtained in Examples 1-5 and Comparative Examples 1-3 was subjected to a photothermal differential scanning calorimetry experiment to study the rapid curing time under ultraviolet irradiation. A Q-2000 differential scanning calorimeter (TA Instruments, USA) was used, equipped with a photothermal device (Novacure 2100), and a 200W medium-pressure mercury lamp was used for irradiation with a wavelength range of 365nm. The ultraviolet irradiation intensity was 5000mW / cm2 on the sample surface for 1 minute. The entire test process was carried out at a temperature of 25°C to eliminate the influence of thermal curing. The time corresponding to the maximum exothermic peak was taken as the photocuring time. The test results are shown in Table 1 below.

[0062] 2. Test of thermal curing time of polymer concrete paste

[0063] The thermal curing time was tested by a penetration test using a Vicat instrument. The polymer concrete slurries obtained in Examples 1-5 and Comparative Examples 1-3 were placed in a cylindrical mold with a bottom diameter of 5 cm and a height of 3 cm, and placed on a horizontal heating table (different temperatures were set at 95°C, 100°C, 120°C, and 135°C) to ensure that the sample surface was flat. The needle of the Vicat instrument was then aligned vertically with the sample surface and adjusted to a free fall of 4 cm from the sample surface to observe the depth of the sample after the pointer stopped being inserted into the sample; measurements were taken every 5 minutes until the insertion depth was 0; the corresponding time was recorded as the thermal curing completion time. The test results are shown in Table 1 below.

[0064] 3. Mechanical properties test of cured polymer concrete paste

[0065] Take samples of Examples 1-5 and undergo photocuring (UV wavelength 365nm, UV intensity 5000mW / cm 2 ) for 15s, and then heat cured at 100°C for 4h to measure the flexural strength and compressive strength. The flexural strength was tested by a three-point bending test. The sample size of Examples 1-5 was cut into 40×10×10mm 3 (length, width, height), set the span to 25mm, and the bending loading rate to 3.0N / s until the specimen breaks. Flexural strength = maximum loading force (N) × span (mm) × 1.25 / (width (mm) × (height (mm)) 2 ). The compressive strength of the samples of Examples 1-5 was tested by uniaxial compression test and cut into 10×10×10 mm 3 (length, width, height), compression loading rate is 30.0N / s, compressive strength = maximum loading force (N) / compression area (mm 2 ). Each measurement was repeated five times, and the test results are shown in Table 1 below.

[0066] Table 1 Basic properties of polymer concrete paste obtained in Examples 1-5 and Comparative Examples 1-3

[0067]

[0068]

[0069] The results in Table 1 show that Examples 1-5 all have both photocuring and thermal curing responses, providing a prerequisite for unsupported 3D printing. The type of cationic photoinitiator, the type of thermal curing agent and the type of aggregate will affect the photocuring efficiency of photo-thermal polymer concrete. Among them, among the types of cationic photoinitiators, triphenyl hexafluoroantimonate sulfonium salt has the fastest photocuring efficiency, and the photocuring time is only 5s, which is conducive to speeding up the printing rate. Among the effects of the type of thermal curing agent on the photocuring efficiency, the boron trifluoride-monoethylamine complex thermal curing agent has the least effect on the photocuring efficiency compared to other thermal curing agents at the same dosage. However, when the dosage of the boron trifluoride-monoethylamine complex thermal curing agent is 10%, the photocuring time is significantly extended. In addition, among the effects of the type of aggregate on the photocuring efficiency, cement aggregates delay the photocuring effect compared to basalt components. This may be because dark cement fillers absorb more ultraviolet light, thereby reducing the light energy available for curing the resin and reducing the photocuring efficiency.

[0070] The heat curing time is closely related to the curing temperature. The curing time is planned to be shortened by half for every 10°C increase in temperature. Compared with Examples 1-4, Comparative Examples 2 and 3 have no photocuring effect, and cannot achieve the unsupported printing process in extreme environments. Comparative Example 1 has no heat curing effect, and the complete curing of the internal structure cannot be achieved by the surface photocuring effect alone. After complete curing, the compressive strength of Examples 1-4 is greater than 120MPa, and the flexural strength is greater than 45MPa, providing high-strength protection for extreme environments. It is worth noting that, as shown in Example 5, when the amount of thermal curing agent is far beyond the reference range provided by the present invention, the thermal curing effect will be greatly accelerated, resulting in a local reaction distance of the polymer, significant heat release, uneven cross-linking degree, and thermal degradation of the epoxy resin, which ultimately significantly deteriorates the mechanical properties of the polymer concrete, with a compressive strength of only 5MPa and a flexural strength of only 2MPa.

[0071] 4. Polymer binder viscosity test

[0072] The viscosity of the polymer binder is mainly determined by the polymer monomer, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate. The viscosity of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate was measured at room temperature of 25°C using an Anton Paar MCR 302 rheometer. When measuring the viscosity, the polymer monomer was introduced into a measuring container with an inner diameter of 39 mm, and the diameter of the tested rotor was 36 mm. The test system was: 10s -1The constant shear rate was about 500 seconds. The final test results showed that the viscosity of 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate was only 1Pa·s at room temperature of 25°C, which is conducive to significantly increasing the amount of inorganic filler and improving the in-situ utilization rate in extreme environments.

[0073] 5. Light-heat dual-curing polymer concrete paste without support 3D printing

[0074] The 3D model was drawn using 3D max software, and the model was exported and poured into a commercial slice processing software. After adjusting the printing parameters, it was exported in .gcode file format to obtain the 3D printed model slice. The light-heat dual-curing polymer concrete slurry synthesized in Example 1 was transferred to the silo of the 3D printer. The printer (such as Figure 1 (As shown in the figure) The extrusion nozzle part is equipped with an ultraviolet light source for the photocuring reaction of the extruded strip. A 200W medium-pressure mercury lamp with a wavelength range of 365nm is used as the ultraviolet light source. The ultraviolet light source is 2cm away from the sample surface, and the ultraviolet light irradiation intensity on the sample surface at this irradiation distance is 5000mW / cm2. A stepper motor is used to control the screw to extrude the light-heat dual-curing polymer concrete slurry, and the screw speed and the printing nozzle movement speed are adjusted to make the slurry evenly deposited on the printing platform. The printing path is automatically set by the slicing software to control the movement speed and distance in the xyz direction of the 3D printer. The movement speed of the 3D printing injection device of the present invention is set to 1mm / s, the screw speed is set to 200mm / min, and the nozzle diameters are set to 2.5mm, 5mm and 8mm respectively. After the light-heat polymer concrete slurry is extruded, it is fixed and formed under ultraviolet light conditions for 5s. After printing is completed, the print is transferred to an oven and heated at 100°C for 4h to achieve full curing. The photocured material is treated with the material and Figure 1 The device shown prints out Figure 2 The thickness of the unsupported printed cantilever beams shown are 2 mm, 4 mm and 6 mm, and the length is 40 cm. Figure 3 The unsupported spiral sphere complex structure shown in the figure has a final structural component with a compressive strength of 131 MPa and a flexural strength of 51 MPa.

Claims

1. A light-heat dual-curing polymer concrete material, characterized in that: The composition comprises the following components in a mass fraction ratio: fine aggregate: polymer monomer: photoinitiator: thermal initiator of 65-75: 25-35: 0.75-2.8: 0.85-2.

8.

2. The light-heat dual-curing polymer concrete material according to claim 1, characterized in that: The polymer monomer is an alicyclic epoxy resin.

3. The light-heat dual-curing polymer concrete material according to claim 2, characterized in that: The polymer monomer is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate.

4. The light-heat dual-curing polymer concrete material according to claim 1, characterized in that: The photoinitiator is at least one selected from onium salt cationic photoinitiators.

5. The light-heat dual-curing polymer concrete material according to claim 4, characterized in that: The onium salt cationic photoinitiator is selected from at least one of triphenyl sulfonium hexafluoroantimonate, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, p-toluenesulfonium sulfonium, phenyldimethyl iodonium, phenethyl iodonium or p-toluene iodonium.

6. The light-heat dual-curing polymer concrete material according to claim 1, characterized in that: The thermal initiator is at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or boron trifluoride-monoethylamine complex.

7. The light-heat dual-curing polymer concrete material according to claim 1, characterized in that: The fine aggregate is one or a mixture of cement, mineral powder, fly ash or ceramic powder.

8. The method for preparing the light-heat dual-curing polymer concrete material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer monomer, photoinitiator and thermal initiator are mixed and stirred to obtain a mixed solution, and then fine aggregate is added to the mixed solution, and stirring is continued until the slurry is mixed evenly.

9. Use of the light-heat dual-curing polymer concrete material according to any one of claims 1 to 7 in 3D printing.

10. A method for 3D printing using the light-heat dual-curing polymer concrete material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) The 3D printer extrusion nozzle is equipped with a UV light source; (2) When the light-heat dual-curing polymer concrete material according to any one of claims 1 to 7 is immediately exposed to ultraviolet radiation after being extruded from the nozzle of a 3D printer, the area on the surface exposed to ultraviolet radiation immediately starts a photocuring reaction to obtain a photocured molded specimen; (3) The photocurable molded specimen obtained in step S2 is heated to perform post-thermal curing treatment to ensure that the areas inside the printed specimen that are not exposed to ultraviolet light are completely cured.

Citation Information

Patent Citations

  • Photo-thermal dual-curing composite direct-writing type 3D printing medium, preparation method and application

    CN114350158A

  • Photo-thermal curing 3D printing photosensitive resin composition and 405nm printing method thereof

    CN118192169A

  • Photo-thermal dual-curing 3D printing resin composite material and application thereof

    CN118290662A